Analisis Kerusakan Mesin Sterilizer Pabrik Kelapa Sawit Menggunakan Failure Modes and Effect Analysis (FMEA) - Wahyuni Amalia; Demi Ramadian; Syarif Nur Hidayat (JTI: Jurnal Teknik Industri, 2022)
Palm Oil Mill is an industry that processes Fresh Fruit Bunches into Crude Palm Oil. The processing is supported by the use of several production machines, one of them is a sterilizer machine that works to boil TBS. Damage to the sterilizer machine can reduce the level of productivity. To overcome the occurrence of such damage, it is necessary to analyze the damage that occurred. Damage analysis was carried out using the Failure Mode and Effect Analysis and Caused and Effect Diagram approaches. From the results of observations and interviews, there are 3 types of damage that often occur. Of the three damages, the type of error that needs to be corrected immediately is based on the value of the Risk Priority Number (RPN), namely damage to the leaky rubber packing door with an RPN value of 85.65. Meanwhile, other types of damage are Leaking Inlet Pipes and detached Aluminum Pipes which have RPN values of 52.48 and 28.9. Based on the analysis of the causes of damage to the rubber packing door, the company can make improvements to the maintenance system, use quality materials, training and socialization, budgeting costs, and monitoring work methods